Blaze loves to race! - Tillworth, Mary; Kobasic, Kevin; Nickelodeon (Firm); Penguin Random House; Random House Children's Books; Viacom International (New York Random House, 2016)
Blaze learns the value of friendship when he rescues several of his truck friends on a racetrack
At head of title: Nickelodeon Blaze and the monster machines
English Stories
Keywords: Monster trucks -- Juvenile fiction; Rescue work -- Juvenile fiction; Trucks -- Juvenile fiction; Monster trucks -- Fiction; Rescue work -- Fiction; Trucks -- Fiction; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Media Tie-In; JUVENILE FICTION -- Transportation; Monster trucks; Rescue work; Trucks; Fiction; Juvenile works